Sellars and Wittgenstein on Following a Rule - Brandt, Stefan (Wilfrid Sellars and Twentieth-Century Philosophy, 2019)
I compare Sellars’s and Wittgenstein’s conceptions of following a rule of language. I begin by briefly speculating about the influence of Wittgenstein’s later writings on Sellars. I then compare the place of rules of language in their respective philosophies. Subsequently, I discuss and compare their notions of following a rule. I conclude by arguing that the differences in their views are the consequence of their different views on the causal role of reasons in the explanation of action.<br